2018
DOI: 10.1007/s11356-018-2033-z
|View full text |Cite
|
Sign up to set email alerts
|

Trends of metals enrichment in deposited particulate matter at semi-arid area of Iran

Abstract: The presence and enrichment of heavy metals in dust depositions have been recognized as an emerging environmental health issues in the urban and industrial areas. In this study, the deposition of some metals was found in Qom, a city located in a semi-desert area in Iran that is surrounded by industrial areas. Dust deposition samples were collected using five sampling stations during a year. Dust samples were digested applying acidic condition and then, the metal content was analyzed using inductively coupled p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The HMs, especially Pb, in road dust can be exchanged continuously between various environmental media like atmosphere, soil, and water 19 . Similarly, it has been reported that inhalation, ingestion, and dermal absorption of road dust can expose human bodies to high concentrations of Pb 20,21 . Another important environmental medium by which Pb can affect human health is soil.…”
Section: Introductionmentioning
confidence: 91%
“…The HMs, especially Pb, in road dust can be exchanged continuously between various environmental media like atmosphere, soil, and water 19 . Similarly, it has been reported that inhalation, ingestion, and dermal absorption of road dust can expose human bodies to high concentrations of Pb 20,21 . Another important environmental medium by which Pb can affect human health is soil.…”
Section: Introductionmentioning
confidence: 91%
“…Qom city is the capital of Qom province and has located 130 km southwest of the capital in the central part of Iran and has an arid and semi-arid climate with an annual rainfall of 161 mm (Fouladi Fard et al, 2018). It has located at 34 • 44' 37'' north latitude, to 55 • 33' 27'' east longitude.…”
Section: Study Areamentioning
confidence: 99%
“…Qom (capital city of Qom province), one of the most populous cities in Iran, is located in the center of Iran with a semi-arid climate (6)(7)(8)(9). Historically, the water supply of Qom has been of great importance due to the arid environment of this city and water scarcity.…”
Section: Study Areamentioning
confidence: 99%